Pharyngeal Carriage Rate of Group A, C and G Streptococci Among Healthy School Children - Demirdağ, Kutbettin; Doğan, Yaşar; Özden, Mehmet; Şen, Yaşar; Aygün, Denizmen; Kalkan, Ahmet (Fırat University, 2001)
Aim: The aim of this study was to determine the pharyngeal carriage rate of group A beta haemolytic streptococci among healthy schoolchildren in Elazig, Turkey. Material and Methods: Throat swabs were taken from 1014 schoolchildren aged 6-15 years and directly were cultured on sheep blood agar plates. Haemolytic streptococci were further identified presumptively using bacitracin (0.04 units), trimethoprim (1.25µg)-sulfamethoxazole (23.75µg) discs and a commercial latex agglutination technique (Dryspot Streptococcal Grouping Kit-Oxoid, England ). Results: The pharyngeal carriage rate of beta haemolytic streptococci was 12.4%, for group A streptococci 9.6%, group C 1.2%, group G 1.6%. None of whom had a sore throat nor signs and/or symptoms of a respiratory tract infection. No sex dependent variations were observed. Conclusion: In conclusion, considering these high rates observed in this study children especially who are going to have medical intervention should be checked with respect to species carriage.

Amaç: Bu çalışmanın amacı; Elazığ'da sağlıklı okul çocuklarında farengeal beta hemolitik streptokok taşıyıcılık oranını belirlemektir. Gereç ve Yöntem: Yaşları 6-15 arsında değişen 1014 öğrenciden boğaz sürüntüleri alındı ve bekletilmeden %5 koyun kanlı agar besiyerine ekimleri yapıldı. Beta hemoliz yapmış olan bakteriler klasik yöntemlerle tanımlandı ve basitrasin (0.04 ünite), trimethoprim (1.25µg)- sulfamethoxazole (23.75µg) diskleri ve ticari latex agglutination kitleri (Dryspot Streptococcal Grouping Kit-Oxoid, England) kullanılarak grup identifikasyonları yapıldı. Bulgular: Taşıyıcılık oranları; BHS %12.4, AGBHS %9.6, C grubu %1.2 ve G grubu %1.6 olarak saptandı. Öğrencilerin hiçbirinde solunum yolu infeksiyonunu düşündürecek belirti ve/veya semptomlar mevcut değildi. Taşıyıcılık oranlarında cinsiyete bağlı değişiklikler gözlenmedi. Sonuç: Sonuç olarak, bu yüksek oranlar dikkate alındığında özellikle tıbbi girişim uygulanacak çocukların taşıyıcılık yönünden araştırılmasının uygun olacağı kanısındayız.
SAĞLIKLI OKUL ÇOCUKLARININ BOĞAZ KÜLTÜRLERİNDE A, C ve G GRUBU STREPTOKOK TAŞIYICILIĞI